KMT9 controls sternness and growth of colorectal cancer - Berlin, Christopher; Cottard, Félicie; Willmann, Dominica; Urban, Sylvia; Tirier, Stephan Marius; Marx, Lisa; Rippe, Karsten; Schmitt, Mark; Petrocelli, Valentina; Greten, Florian R.; Fichtner-Feigl, Stefan; Kesselring, Rebecca; et al. (Cancer research, 2022)
Colorectal cancer is among the leading causes of cancer-associated deaths worldwide. Treatment failure and tumor recurrence due to survival of therapy-resistant cancer stem/initiating cells represent major dinical issues to overcome. In this study, we identified lysine methyltransferase 9 (KMT9), an obligate heterodimer composed of KMT9 alpha and KMT9 beta that monomethylates histone H4 at lysine 12 (H4K12mel), as an important regulator in colorectal tumorigenesis. KMT9 alpha and KMT9 beta were overexpressed in colorectal cancer and colocalized with H4K12me1 at promoters of target genes involved in the regulation of proliferation. Ablation of KMT9 alpha drastically reduced colorectal tumorigenesis in mice and prevented the growth of murine as well as human patient-derived tumor organoids. Moreover, loss of KMT9 alpha impaired the maintenance and function of colorectal cancer stem/initiating cells and induced apoptosis specifically in this cellular compartment. Together, these data suggest that KMT9 is an important regulator of colorectal carcinogenesis, identifying KMT9 as a promising therapeutic target for the treatment of colorectal cancer. Significance: The H4K12 methyltransferase KMT9 regulates tumor cell proliferation and sternness in colorectal cancer, indicating that targeting KMT9 could be a useful approach for preventing and treating this disease.
Published Online First: November 4, 2021
Gesehen am 11.02.2022